Biorefineries Selected Processes - Biernat, Krzysztof (IntechOpen, 2022)
This book presents selected processes that can be applied in contemporary and future biorefinery systems. It discusses the indicators characterizing the level of sustainable development for these systems as well as the methods of segregation and purification of biorefinery products, the use of enzymes, the possibility of obtaining bioplastics, ethyl alcohol, and co-pyrolysis of coal and biomass. This book is a valuable resource for research teams working on the development of biorefinery technologies as well as teachers and students of biotechnology faculties.